FINANCIAL ANALYSIS OF THE HOUSEHOLD INDUSTRY'S PALM SUGAR IN LETTA VILLAGE, LEMBANG DISTRICT, PINRANG CITY - Jumaria Jumaria; Iranita Haryono; Fitriani R; Muhammad Rais Rahmat Razak (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
One of the most appropriate efforts in economic empowerment is to develop economic activities that become the basis of the economic life of all people and are able to accommodate existing human resources. Financial analysis aims to assess whether a particular activity being carried out is financially feasible, or can provide financial benefits for the business which aims to maximize profits. This research aims to determine the financial feasibility of home industry palm sugar in Letta Village, Lembang District, Pinrang Regency by calculating the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Profitability Index (PI). This type of research is quantitative research with survey methods. The sample in this research was 1 palm sugar craftsman in Letta Village, Lembang District, Pinrang Regency with a sampling technique, namely using a Purposive Sampling technique or deliberately using certain criteria. The data analysis technique used is feasibility analysis. The results of the research show that the home industry palm sugar business in Letta Village, Lembang District, Pinrang Regency is financially feasible to operate because the Net Present Value (NPV) value is IDR 153,231,875, the Internal Rate of Return (IRR) is 47% with a level of interest rate of 15%, Profitability Index (PI) 1.00, which is 5.03%, and the Payback Period (PP) obtained in the home industry palm sugar business is 2 months 3 weeks, the time required to return business capital.